2017
DOI: 10.5296/jas.v5i3.11637
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seed Priming on Biochemical Changes in Fresh and Aged Seeds of Cucumber

Abstract: The present investigation was conducted at the laboratory of Seed Science and Technology, Indian Institute of Horticultural Research, Hessaraghatta, and Bangalore, India during March 2014 to September 2014. The objective of the study was to identify effect of seed priming on biochemical changes in cucumber seeds. This study showed that the enhancement in seed viability and vigor in primed seeds was due to low membrane injury coupled with high enzyme activities (dehydrogenase and amylase). respectively in cucum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
4
2
0
1
Order By: Relevance
“…In similar ndings, it was hypothesized that the extra peptide could be a peptide of 2S albumin with Mw 4-10 kDa 49 . Similar trends were reported in cucumber 35 and black beans 50 . The probable reason for the extra one band in all treated seeds is priming, resulting in the synthesis of lost proteins and some new ones.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In similar ndings, it was hypothesized that the extra peptide could be a peptide of 2S albumin with Mw 4-10 kDa 49 . Similar trends were reported in cucumber 35 and black beans 50 . The probable reason for the extra one band in all treated seeds is priming, resulting in the synthesis of lost proteins and some new ones.…”
Section: Discussionsupporting
confidence: 86%
“…The present study observed a relatively high amount of dehydrogenase after priming. Similar trends were reported in cucumber 35 and cowpea 36 , suggesting the role of priming in accelerating dehydrogenase activity.…”
Section: Discussionsupporting
confidence: 81%
“…( 2002) and ( 2009) reported that hydropriming treatment can be successfully applied to watermelon and cucumber seeds to improve germination performance, respectively. Primed seeds further exhibited tolerance to abiotic stress conditions (high temperature and water stress) as evident from higher germination compared to unprimed (Pandey et al, 2017).…”
Section: Germination Percentagementioning
confidence: 99%
“…De acordo com Mal et al (2018) o condicionamento de sementes é uma técnica pós-colheita e pré-semeadura que pode melhorar o vigor de sementes, sendo promissora para incrementar a taxa de uniformidade do plantio (PANDEY et al, 2017).…”
Section: Introductionunclassified